2014
DOI: 10.1016/j.polymertesting.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated ageing and lifetime prediction of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) in distilled water

Abstract: International audienceAccelerated ageing was performed in distilled water at different temperatures (25, 30, 40 and 50°C) on poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), which is a biodegradable biopolymer, in order to estimate its lifetime in aqueous environment. In a first part, degradation mechanisms were followed by gravimetry, tensile tests and steric exclusion chromatography. Both immersion and relative humidity have been examined. In a second part, the strain at break was used as an indicator fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 34 publications
3
47
0
Order By: Relevance
“…In this sense, both agents, water and temperature can sinergically act to simulate real service conditions. This has been reported for neat [219], [220] and reprocessed PLA [221], [222], PHAs [223], [224], PCL, and blends [225] or composites such as PLA/sisal [226], [227], PHBV/sisal [228], or poly(butylene sebacate) (PBS)/montmorillonite [229], among others.…”
Section: Hydrolytic and Hydrothermal Degradationmentioning
confidence: 60%
“…In this sense, both agents, water and temperature can sinergically act to simulate real service conditions. This has been reported for neat [219], [220] and reprocessed PLA [221], [222], PHAs [223], [224], PCL, and blends [225] or composites such as PLA/sisal [226], [227], PHBV/sisal [228], or poly(butylene sebacate) (PBS)/montmorillonite [229], among others.…”
Section: Hydrolytic and Hydrothermal Degradationmentioning
confidence: 60%
“…This could be related to the increased crystallinity and subsequently increase in modulus . A number of researchers have observed a similar tendency in the modulus after exposure to different weathering conditions . These studies were concluded that the modulus improvement of the conditioned samples is associated with structural relaxation, increase in crystallinity, crystal perfection, and increase of lamella thickness.…”
Section: Resultsmentioning
confidence: 86%
“…The durability of the polymers and composites is strongly related to the degradation mechanism. The degradation mechanism is a key factor for the lifetime prediction of polymeric materials . If the polymeric materials maintain their required mechanical performance at least 60 weeks at elevated temperature (50°C) and humidity (90%) it may be used for 10 year durable applications .…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights and confirms an entire bioassimilation of the PHBV film in natural environment thanks to the bacterial attacks on the surface. As recently published [38], the ageing of PHBV was also studied in distilled water and the results indicated that no surface erosion was detected in the absence of bacteria and / or microorganisms. The PHBV biodegradation in natural environments is therefore initiated by the enzymatic hydrolysis reaction with PHA-degrading enzymes.…”
Section: Liquid Inoculum: Seawater Loadedmentioning
confidence: 75%